A) -137-(-4) do potęgi 3 =
b) -[-(-5) do potęgi 2 + (-1) do potęgi 3]=
c) -28+12 * (-0,5)do potęgi 2 - 6 * (-1/2) =
d) -(-1/2) do potęgi 3 + (-0,4)do potęgi 3 : (1 i 1/5) * 2 i 13/16=
e) (-0,25)do potęgi 2 : (-1/8) : (-2)do potęgi 2 -(-1000)
f) (-3,2) + (-2)do potęgi 5 * (1/2 * 5/8)- (-0,8)
g) -2 do potęgi 2 - (13*7do potęgi 2) - (0,1 do potęgi 3) * 10 do potęgi 3

1

Odpowiedzi

2010-02-09T22:00:46+01:00
A) = (-137+64)= -73
b) -[-25-1]= 25-1=24
c) = -28+12*0,25-6* (-1/2)= -28+3+3=22
d) (-1/2-0,064): (6/5 *45/16)= (-0,5-0,064) : 27/8= -0,5- 0,064*27/8= -0,5-0,064*3,375=-0,5-0,216=-0,716
e)0,5:(-1/8):4+1000=0,5*(-8):4+1000=-4:4+1000=-1+1000=999
f)(-3,2)-32*20/8+0,8=(-3,2)-80+0,8-82,4
g)-4-8281-0,001*1000= -4-8281-1=-8286